2009
DOI: 10.2105/ajph.2008.139329
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Social Networks With High Rates of Undiagnosed HIV Infection: The Social Networks Demonstration Project

Abstract: Objectives. We evaluated the use of social networks to reach persons with undiagnosed HIV infection in ethnic minority communities and link them to medical care and HIV prevention services. Methods. Nine community-based organizations in 7 cities received funding from the Centers for Disease Control and Prevention to enlist HIV-positive persons to refer others from their social, sexual, or drug-using networks for HIV testing; to provide HIV counseling, testing, and referral services; and to link HIV-positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 7 publications
4
122
1
3
Order By: Relevance
“…Social networks recruited the fewest number of women, yet this strategy was most likely to find women who engaged in very high-risk sex and drug use behaviors. These findings are similar to those reported by Kimbrough et al (2009), whose research showed that social networks were very effective in recruiting persons in high-risk networks. Published studies have reported similar findings that support using social networks to reach persons at high risk for HIV and other STDs (Halkitis et al, 2011;Rothenberg et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Social networks recruited the fewest number of women, yet this strategy was most likely to find women who engaged in very high-risk sex and drug use behaviors. These findings are similar to those reported by Kimbrough et al (2009), whose research showed that social networks were very effective in recruiting persons in high-risk networks. Published studies have reported similar findings that support using social networks to reach persons at high risk for HIV and other STDs (Halkitis et al, 2011;Rothenberg et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Women reached through social networks were most likely to report nonpermanent housing, unprotected sex with a male of known HIV risk, and drug use. Furthermore, the social network strategy is an especially important public health tool because the same social networks through which HIV infection occurs can be accessed for early detection and prevention of new infections (Adimora & Schoenbach, 2005;CDC, 2005;Kimbrough et al, 2009). A recent evaluation of multiple recruitment strategies to identify HIV-positive African American men who have sex with men (MSM) for HIV testing found social networks to be most effective, followed by partner services and alternate venues (Halkitis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that the social networks strategy may be an effective method for identifying persons with undiagnosed sexually transmitted infections, including HIV [22][23][24][25]. In the social networks strategy, HIV testers and agency staff engage either HIV-positive individuals or those at high risk of seroconversion to become "recruiters."…”
Section: Introductionmentioning
confidence: 99%
“…45 Many of the implementation challenges highlighted by these demonstration projects and other published studies examining various HIV testing strategies readily lend themselves to OR. 46,47 At a minimum, OR must identify optimal strategies for reaching high-risk persons to increase early detection, receipt of test results, and linkage to medical care. Effective strategies must be developed and disseminated to ensure that persons who receive preliminary test results also receive confirmatory results, to enhance partner services programs to identify new HIV-positive persons, and to strengthen the implementation of self-testing.…”
Section: Hiv Testing In Clinical and Nonclinical Settingsmentioning
confidence: 99%